Anti-Aggressive Accounting Creative Pada Lembaga Perkreditan Desa Menuju Pembangunan Inklusif Berkelanjutan - Darmayasa, I Nyoman; I Ketut Suwintana; Ni Nyoman Harini Puspita; I Made Agus Putrayasa; I Ketut Parnata; I Made Bagiada; Ni Luh Putri Setyastrini; Ketut Nurhayanti; Putu Adi Suprapto; Ni Komang Urip Krisna Dewi (Politeknik Negeri Jember, 2024)
This study aims to understand the meaning of aggressive accounting creative practices in Village Credit Institutions (LPD). This study involved four participants from LPD empowerment services and institutions, academics, and three LPD heads. Data were collected through in-depth interviews, followed by data triangulation (source, technique, and time) based on Miles and Huberman's interactive analysis. Interpretive analysis was used for data analysis. This study found the existence of aggressive creative accounting practices, which means maintaining stakeholder trust so that the level of health and risk of LPDs is maintained. New meaning of anti-aggressive creative accounting through digital transformation of reporting in the form of accrual income recognition and cash adjustments. Digital transformation is described through the technology acceptance model (TAM) theory, which can be explained using stakeholder theory and agency theory with the additional assumption of intentional human beings extending human local values. The research contribution is theoretically in the form of developing theoretical assumptions and practically to prevent aggressive accounting creativity so that sustainable inclusive development from villages towards Indonesia can be realized.